2016
DOI: 10.35790/ecl.4.1.2016.11034
|View full text |Cite
|
Sign up to set email alerts
|

Profil Pasien Hipertensi Di Poliklinik Ginjal-Hipertensi

Abstract: : Hypertension is chrocnic medical condition which the blood pressure has elevated above 140mmHg systolic and 90 mmHg diastolic. Hypertension is one of top 10 of the causes of death worldwide. It is because hypertension affects in damaged of some organs like heart, brain, renal, retinal, ect.The purpose of this study is to give the information about profile of hypertensive patients and about antihypertensive drugs which most commonly used in Prof. Dr. R. D. Kandou General Hospital Manado.This is descriptive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…The number of anti-HT consumed by CKD patients in this study was at most 1 drug or monotherapy (74.7%). This is in accordance with previous studies which showed that the use of anti-HT monotherapy was more widely used in prehypertension, controlled HT, and grade 1 HT (Tandililing et al, 2017;Fadhilla and Permana, 2020;Tamburian et al, 2016;Liu et al, 2016;Marinier et al, 2019). Anti-HT monotherapy can still treat controlled HT and HT grade 1, while HT grade 2 requires combination therapy (Tandililing et al, 2017;Marinier et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The number of anti-HT consumed by CKD patients in this study was at most 1 drug or monotherapy (74.7%). This is in accordance with previous studies which showed that the use of anti-HT monotherapy was more widely used in prehypertension, controlled HT, and grade 1 HT (Tandililing et al, 2017;Fadhilla and Permana, 2020;Tamburian et al, 2016;Liu et al, 2016;Marinier et al, 2019). Anti-HT monotherapy can still treat controlled HT and HT grade 1, while HT grade 2 requires combination therapy (Tandililing et al, 2017;Marinier et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The highest degree of HT in this study was controlled HT (66.7%) <140 mmHg/<90 mmHg. This is in line with the research of Tamburian et al, 2016 which showed that controlled HT was more than uncontrolled HT, and there were more patients without complications. The study of Dramawan, 2017 also shows that HT is controlled more and the highest age group is 46-55 years old, meaning that the older you are, the wiser you will be and there will be more information about the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation